The importance of breaststroke glide times - Chollet, D.; Chollet, D.; Leblanc, H.; Guignard, B.; Seifert, L. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The specificity of cyclic activities is characterized by the fact that locomotor displacement is achieved by the realization of a motricity reproduced in an identical or similar manner (cycle). Human locomotion is cyclical by nature and includes walking, running, cycling, rowing, ice or roller skating, etc. While cyclical activities are intrinsically "continuous", each of its locomotor cycle can be broken down into "phases". The term "sliding sport" defined as: "all sports involving gliding (skiing, windsurfing, surfing, etc.)" appears fairly restrictive. However, many physical and sporting activities can be considered to be cyclical and gliding, as in the case of ice skating, roller skating, cycling, canoeing, kayaking and swimming. Breaststroke in particular, like cross-country skiing, appears to be a cyclical gliding activity insofar as gliding phases play a predominant role. Even at high stroke paces, there is a substantial glide time that follows the propulsive phase of the legs allowing the breaststroke swimmers to take advantage of this propulsion to keep moving forward. This glide time depends on swimming speed, level of expertise and gender. Alternating propulsion and gliding phases are crucial to performance, particularly in breaststroke, to avoid the accordion effect achieved by beginners, i.e. a coordination pattern where the legs extension and flexion respectively. The burst-and-coast model for swimmer intra-cycle velocity variations (Carmigniani et al, 2020) highlights the alternation of propulsive and glide phases. This seems similar to the burstand-coast swimming behavior observed for certain fish such as cod or saithe. They found that if the fish had a reduced drag during the glidin phase they could consume less mechanical energy to maintain the same average velocity than in steady swimming. Measuring the duration of the gliding phase and its timing in relation to the other phases of the cycle enables us to assess its importance, particularly the gliding phase that follows the propulsion of the legs. The purpose of this study is to examine the changes in arm and leg coordination in breaststroke over three increasing swimming speeds and to compare these changes among current elite swimmers.